Answer:
b= -10
Step-by-step explanation:
9^ -8 * 9^ -2
We know that a^b * a^c = a^ (b+c)
9^ (-8+-2)
9^ -10
We want it in the form a^b
a=9
b= -10
Could you send a picture of the question
Your answer would be the last option, c = √(E/m).
We can see this when we rearrange the equation, as:
E = mc²
÷ m
E/m = c²
√
√(E/m) = c
So you got all the steps in rearranging correct :)
I hope this helps!
Answer:
t does not matter if the two numbers are the same for multiplication or division. 4. ( ÷ ) To divide two fractions, take the second fraction, and flip it so that the top number is now on the bottom and vice versa, then multiply the two fractions together like you would for number 3.
Step-by-step explanation: